KELOMPOK YANG DIBUNGKAM DALAM RETORIKA DR. REISA, WANITA SEBAGAI JURU BICARA PEMERINTAH INDONESIA - EPIDEMIS COVID-19 (ANALISIS WACANA KRITIS SARA MILLS) - Arfika Pertiwi putri (LPPM Universitas Negeri Surabaya, 2024)
The government has a big role in handling the Covid-19 pandemic. In his duties, dr. Reisa Broto Asmoro provided information related to the development of the Covid-19 pandemic in Indonesia in the form of speeches and questions and answers. In “The Second Stage”, Friedan (1980) encouraged women to become women. Now women have obtained the same rights as men, one of which is in the public space. Cheris Kramarae (1981) states that the language of a particular culture does not support all speakers equally. The purpose of this study is to determine the existence of women's gender equality in the public sphere. Research using Sara Mills critical discourse analysis with rhetoric theory, this silent group theory concludes that in the rhetoric delivered by dr. Reisa Broto Asmoro still shows the clear dominance of male perceptions and then inhibits women's expression of the world. Female characteristics are not accepted by the public. This shows that women until now to be able to participate in society, they have to transform the model according to the male expression system even though the pathos, ethos and logos of women have evidence in rhetoric and rhetorical sensitivity. Ironically, silencing is not only from the dominant but also from fellow women. Even though there has been gender equality, there is still implicit oppression of silence. Keywords: Rhetoric; Covid-19; Sara Mills; Feminism; Muted Group